Analysing the challenges, barriers and risks of e-governance for efficient and effective governance - Kalsi, Singh Nairmaljeet and Kiran, Ravi (Productivity)
Information & Communication Technologies (ICTs) make a difference in the way citizens can realise these services. Therefore, it is essential to examine the elements contributing to the suffering and harassment of residents, enabling effective intervention and enhancing government services. This study employs a participatory stakeholder analysis to examine these aspects. An effort is made to rank these based on mean scores after using factor analysis for factor reduction. The researchers attempt to examine the average scores of academicians and policymakers to ascertain any differences in opinion between the two groups about pain and harassment elements. The purpose of this paper is to expand upon previous research on the topic of e-governance obstacles so that potential solutions can be considered for efficient governance.-Reproduced